Penilaian Kinerja Keuangan Koperasi Di Kabupaten Pelalawan - Dahlan Tampubolon; Yusbar Yusuf; Elida Ilyas (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2009)
This paper describe development and financial performance of cooperative in District Pelalawan among 2007 - 2008. Studies on primary and secondary cooperative in 12 sub-districts. Method in this stady use performance measuring of productivity, efficiency, growth, liquidity, and solvability of cooperative. Productivity of cooperative in Pelalawan was highly but efficiency still low. Profit and income were highly, even liquidity of cooperative very high, and solvability was good.